Participatory Evaluation of Oat and Vetch Varieties under Farmers Management in Bulle Highland, Southern Ethiopia (Global Journal of Science Frontier Research, 2021)
Five oat and three vetch varieties were demonstrated and evaluated under farmers' management conditions at Seka kebele of Bulle Woreda, southern Ethiopia, with the objective of introduction and evaluation of different Oat Vetch species. The oat varieties were Lampton (standard check), CI-2291, CI-8251, CI-8237, and CI-2806, whereas the vetch varieties evaluated were Vicia dasycarpa (V.D), Vicia Sativa (V.S), and Vicia villosa. The varieties were planted in a 3 m x 4 m plots arranged in an RCBD design with four replications. The results indicated that the germination date was influenced by the effect of the year. Accessions like CI-2291 and CI-2806 had higher (p≤0.05) dry matter yield than other accessions regardless of year effect, while accession CI-8251 and CI-8237 had higher seed yield than other accessions. Regarding vetch varieties, Vicia sativa had a significantly (P
Keywords: dry matter yield; oat; vetch; adaptability; varieties; seed yield